2020
DOI: 10.1007/s00402-020-03395-6
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal effect on the incidence of post-operative wound complications after trauma-related surgery of the foot, ankle and lower leg

Abstract: Introduction Post-operative wound complications remain among the most common complications of orthopedic (trauma) surgery. Recently, studies have suggested environmental factors such as season to be of influence on wound complications. Patients operated in summer are reported to have more wound complications, compared to other seasons. The aim of this study was to identify if "seasonality" was a significant predictor for wound complications in this cohort of trauma-related foot/ankle procedures. Materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Spinal surgery, total joint replacement, as well as foot and ankle surgery carried out in summer were associated with a higher risk of surgical site complications compared with winter. [24][25][26][27] However, the association between season and systemic complications or mortality remains unknown in hip fracture surgery. Observational studies in Europe and Asia showed a higher incidence of hip fracture in winter.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal surgery, total joint replacement, as well as foot and ankle surgery carried out in summer were associated with a higher risk of surgical site complications compared with winter. [24][25][26][27] However, the association between season and systemic complications or mortality remains unknown in hip fracture surgery. Observational studies in Europe and Asia showed a higher incidence of hip fracture in winter.…”
Section: Discussionmentioning
confidence: 99%
“… 11 No effect of season has been noted on post-operative wound complications after trauma to the foot, ankle or lower leg. 12 Another study found no difference in seasonal variation of complications 30 days after THA. 13 Taken as a whole, the body TJA literature remains inconclusive on the role of season of index surgery on outcomes.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, we conducted a review similar to the review of Backes et al, 4) where we collected data regarding POWCs and infections for surgery via STA whilst combining it with geographical differences including differences in climate. 13 14) Additionally, the correlations between the mean temperature of a country, frequency of performed surgeries, and functional outcome scores were analyzed in order to explain possible differences found between individual countries. 13 14) …”
mentioning
confidence: 99%
“… 13 14) Additionally, the correlations between the mean temperature of a country, frequency of performed surgeries, and functional outcome scores were analyzed in order to explain possible differences found between individual countries. 13 14) …”
mentioning
confidence: 99%